2004
DOI: 10.1158/1078-0432.ccr-03-0528
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Epithelial Cell Adhesion Molecule Antigen in Gallbladder Carcinoma Is an Independent Marker for Poor Survival

Abstract: Purpose: Gallbladder carcinoma is an aggressive type of cancer that is difficult to cure by conventional procedures. There thus is a need to identify novel molecular markers for the assessment of prognosis and as potential therapeutic targets. This retrospective study was designed to investigate the prognostic significance of epithelial cell adhesion molecule (Ep-CAM) overexpression in human gallbladder carcinoma.Experimental Design: Ep-CAM expression was examined immunohistochemically on paraffin-embedded tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
104
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(111 citation statements)
references
References 21 publications
5
104
1
1
Order By: Relevance
“…Efforts for standardising the immunohistochemical staining and evaluation procedure were explained highlighting an advanced scoring system that reflected both frequency, and intensity of staining. A similar negative correlation between EpCAM expression and survival as previously observed by the group for breast and gall bladder cancer (Varga et al, 2004) was also now observed with ampullary carcinoma of the pancreas (Fong et al, 2006) and for squamous cell cancer of head and neck. N Stoecklein (Duesseldorf, Germany) reported a negative correlation between EpCAM expression and overall survival in patients with squamous cell carcinoma of the oesophagus, a very deadly disease with no established systemic treatment option.…”
Section: Epcam Expression and Survival Prognosis Of Cancer Patientssupporting
confidence: 86%
“…Efforts for standardising the immunohistochemical staining and evaluation procedure were explained highlighting an advanced scoring system that reflected both frequency, and intensity of staining. A similar negative correlation between EpCAM expression and survival as previously observed by the group for breast and gall bladder cancer (Varga et al, 2004) was also now observed with ampullary carcinoma of the pancreas (Fong et al, 2006) and for squamous cell cancer of head and neck. N Stoecklein (Duesseldorf, Germany) reported a negative correlation between EpCAM expression and overall survival in patients with squamous cell carcinoma of the oesophagus, a very deadly disease with no established systemic treatment option.…”
Section: Epcam Expression and Survival Prognosis Of Cancer Patientssupporting
confidence: 86%
“…The emerging functional importance of Ep-CAM for tumour cells would be more consistent with the phenotype of breast and gall bladder cancers, where Ep-CAM overexpression is an independent predictor of poor survival Varga et al, 2004). Overexpressed Ep-CAM was shown to provide a potent growth stimulus to tumour cells enabling proliferation , and led to an increased invasiveness and migration of tumour cells presumably due to Ecadherin antagonism (Litvinov et al, 1997;Osta et al, 2004).…”
Section: Discussionmentioning
confidence: 74%
“…Previous studies investigated the influence of Ep-CAM expression on survival in a number of other carcinoma. Epithelial cell adhesion molecule upregulation was an independent marker for poor survival in lymph node positive breast cancers , and gall bladder cancers (Varga et al, 2004). In contrast, improved survival was found associated with Ep-CAM upregulation in clear cell renal cell carcinoma (Kim et al, 2004;Seligson et al, 2004;Went et al, 2005), and gastric cancers (Songun et al, 2005).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…We recently showed that EpCAM (TROP1, GA733-2) overexpression predicts poor survival in different cancer entities. [14][15][16] Interestingly, expression of TROP2 did not correlate with EpCAM expression. 17 Anti-EpCAM antibodies can cause significant reduction in mortality and relapse rates of resected colon cancer patients following treatment with the EpCAM-specific monoclonal antibody edrecolomab.…”
Section: Discussionmentioning
confidence: 96%